Analysis of company performance measurement using Green Supply Chain Management Method on bussiness unit of black tea - Ikhda Nikmatul Mukharromah; Panji Deoranto; Siti Asmaul Mustamiroh; Kralawi Sita (Research Institute for Tea and Cinchona, 2017)
Competition black tea bussiness currently is no longer competition between companies but competition in supply chain network. PPTK Gambung as company and research institution that manage business unit of black tea so far nor been the identification of performance indicators Green Supply Chain Management (GSCM), to understand the condition of black tea business unit performance integrated overall both the process and operation. The aim of this study which provides recommendations for improvement to the company in improving the performance of the bussiness unit of black tea which has not reached the expected target. Performance measurement in this study using GSCM involving Analytical Hierarchy Process (AHP) for weighting KPI, Scoring System method Objectives Matrix (OMAX), and Traffic Light System (TLS) to analyze the scores of environmental performance assessment are classified by color. The aim of this study which provides recommendations for improvement to the company in improving the performance of which has not reached the expected target. From the result, it can be seen that Index Performance Indicator is 5,35 company which means the PPTK Gambung performance has yet to be reached despite the are approaching the target,. Based on the results obtained 31 KPI valid OMAX which consists of 18 KPI that have reached the target; 1 KPI has yet to be reached despite the are approaching the target and 11 KPI that have a performance targetless. Based on these results can be made efforts to improve the performance of the company by making an integrated measurement that includes all existing processes (upstream - downstream) and periodically for maximum performance can be achieved, so it can be a consideration and evaluation for the company to overcome the performance problems companies either preventive action or corrective action.